Injury risk associated with playing actions during competitive soccer. Issue 5 (1st October 2002) - Rahnama, N; Reilly, T; Lees, A
Abstract : Objective: To assess the exposure of players to injury risk during English Premier League soccer matches in relation to selected factors. Methods: Injury risk was assessed by rating the injury potential of playing actions during competition with respect to ( a ) type of playing action, ( b ) period of the game, ( c ) zone of the pitch, and ( d ) playing either at home or away. In all, 10 games from the English Premier League 1999–2000 were chosen for analysis. A notation system was used whereby 16 soccer specific playing actions were classified into three categories: those inducing actual injury, those with a potential for injury (graded as mild, moderate, or high), and those deemed to have no potential for injury. The pitch was divided into 18 zones, and the position of each event was recorded along with time elapsed in the game, enabling six 15 minute periods to be defined. Results: Close to 18 000 actions were notated. On average (mean (SD)), 1788 (73) events (one every three seconds), 767 (99) events with injury potential (one every six seconds), and 2 (1) injuries (one every 45 minutes) per game were recorded. An overall injury incidence of 53 per 1000 playing hours was calculated. Receiving a tackle, receiving a "charge", and making a tackle were categorised as having a substantial injury risk, and goal catch, goal punch, kicking the ball, shot on goal, set kick, and heading the ball were all categorised as having a significant injury risk. All other actions were deemed low in risk. The first 15 minutes of each half contained the highest number of actions with mild injury potential, the last 15 minutes having the highest number of actions with moderate injury potential (p<0.01). The first and last 15 minutes of the game had the highest number of actions with high injury potential, although not significant. More actions with mild injury potential occurred in the goal area, and more actions with moderate and high injury potential occurred in the zone adjacent to the goal area (p<0.001). There was no significant difference between home and away with regard to injury potential. Conclusions: Playing actions with high injury risk were linked to contesting possession. Injury risk was highest in the first and last 15 minutes of the game, reflecting the intense engagements in the opening period and the possible effect of fatigue in the closing period. Injury risk was concentrated in the areas of the pitch where possession of the ball is most vigorously contested, which were specific attacking and defending zones close to the goal. Injury potential was no greater in away matches than at home.